2007
DOI: 10.1080/07399330601180206
|View full text |Cite
|
Sign up to set email alerts
|

Bridges and Barriers to Health: Her Story—Emirati Women's Health Needs

Abstract: Health care services in the United Arab Emirates have developed rapidly in the last 30 years fueled by oil revenues. These services have been planned and provided predominantly by non-nationals, with mixed success. The authors identify aspects of the health care system and the sociocultural environment that create both barriers and bridges to holistic health for Emirati women. Barriers include early/consanguineous marriage, frequent childbearing, polygamy, and care that is lacking in competence and cultural se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 47 publications
1
22
0
Order By: Relevance
“…We found that the Muslim women in our study, irrespective of their age, marital status, income, and literacy status, almost exclusively requested a female physician for medical conditions involving the awrah, areas of the body required by Islam to be covered, and which Muslim women generally find embarrassing to expose to the opposite gender (Underwood et al, 1999;Winslow & Honein, 2007;Yosef, 2008). Our findings confirm reports of Muslim women's request for same-gender physicians in O&G (Aldeen, 2007;Hammoud et al, 2005;Lafta, 2006;Rizk et al, 2005;Rizk & El-Safty, 2006;Uskul & Ahmad, 2003).…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…We found that the Muslim women in our study, irrespective of their age, marital status, income, and literacy status, almost exclusively requested a female physician for medical conditions involving the awrah, areas of the body required by Islam to be covered, and which Muslim women generally find embarrassing to expose to the opposite gender (Underwood et al, 1999;Winslow & Honein, 2007;Yosef, 2008). Our findings confirm reports of Muslim women's request for same-gender physicians in O&G (Aldeen, 2007;Hammoud et al, 2005;Lafta, 2006;Rizk et al, 2005;Rizk & El-Safty, 2006;Uskul & Ahmad, 2003).…”
Section: Discussionmentioning
confidence: 94%
“…2002) or in Islamic countries (Lafta, 2006; Downloaded by [New York University] at 00:55 06 October 2014 Rizk et al 2005;Rizk & El-Safty, 2006;Rizk, Nasser, Thomas, & Ezimokhai, 2001;Rizk, Shaheen, Thomas, Dunn, & Hassan, 1999;Uskul & Ahmad, 2003;Winslow & Honein, 2007). Thus, in contexts and communities where culture and religion are deep rooted, a same-gender practitioner is likely to be important for women, particularly for intimate examinations such as breast, obstetric, gynecological, and urogenital examinations (Aldeen, 2007;Matin & LeBaron, 2004;Rajaram & Rashidi, 1999Rizk & El-Safty, 2006;Rizk et al, 2001Rizk et al, , 2005Underwood et al, 1999;Zuckerman et al, 2002).…”
Section: Women's Physician Preferencementioning
confidence: 94%
See 3 more Smart Citations